Modified polyvinyl alcohol resin with improved solubility in alcohol mixtures

JP2025502968APending Publication Date: 2025-01-30SEKISUI SPECIALTY CHEMICALS AMERICA LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024542073
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-14
Filing Date
2023-01-13
Publication Date
2025-01-30

AI Technical Summary

Benefits of technology

【0008】 特許請求される主題の他の態様及び利点は、以下の説明及び添付した特許請求の範囲から明らかになるであろう。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025502968000001_ABST
    Figure 2025502968000001_ABST
Patent Text Reader

Abstract

The sulfonic acid modified polyvinyl alcohol resin contains up to 15 mol% of a first comonomer containing a sulfonic acid group. The modified polyvinyl alcohol resin has a hydroxyl unit content of at least 65 mol% and a gel fraction of 3.2 or less. Furthermore, the modified polyvinyl alcohol resin has a disintegration time of 85 seconds or less measured at 23°C in a mixture of 50 vol% water and 50 vol% isopropyl alcohol. In addition, the modified polyvinyl alcohol resin has a hard component present in a component ratio of 10% to 55% and has a relaxation time of 0.0091 ms to 0.0104 ms measured at 80°C by pulse NMR solid echo method. A method for producing the sulfonic acid modified polyvinyl alcohol resin is also disclosed, and the resin can be advantageously used in inks, paints, paper coatings, emulsions, or films.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates generally to modified polyvinyl alcohol resins, and more particularly to modified polyvinyl alcohol resins having improved solubility in alcohol mixtures. [Background technology]

[0002] Copolymers of polyvinyl alcohol (PVOH) and 2-acrylamido-2-methylpropanesulfonic acid (AMPS), either in the free acid form or as a salt of the free acid, are known in the art and are referred to as PVOH-co-AMPS copolymers. These copolymers are commonly used to form water-soluble films for unit dose packaging of detergents and harsh substances due to their excellent cold water solubility and resistance to oxidizing substances.

[0003] However, sulfonated PVOH copolymers such as PVOH-co-AMPS do not have good solubility in solutions containing alcohol, such as alcohol mixed with water. There are industrial applications that would benefit from having sulfonated PVOH with improved solubility in alcohol mixtures, including, but not limited to, inks, paints, paper coatings, emulsions, and film formulations. Summary of the Invention [Means for solving the problem]

[0004] This summary introduces some of the concepts that are further described below in the Detailed Description. This summary is not intended to identify key or essential features of the claimed subject matter, nor is it intended to be used as an aid in limiting the scope of the claimed subject matter.

[0005] In one aspect, the embodiments disclosed herein relate to a sulfonic acid modified polyvinyl alcohol resin comprising 0.1-15 mol % of a first comonomer comprising a sulfonic acid group. The modified polyvinyl alcohol resin has a hydroxyl unit content of at least 65 mol % as measured by NMR, and a gel fraction of 3.2 or less. Furthermore, the modified polyvinyl alcohol resin has a disintegration time of 85 seconds or less as measured at 23°C according to the Solution Cast Disintegration Test Method in a mixture of 50 vol % water and 50 vol % isopropyl alcohol. In addition, the modified polyvinyl alcohol resin has a hard component present in a component ratio of 10% to 55% and having a relaxation time of 0.0091 ms to 0.0104 ms as measured at 80°C by pulse NMR solid echo method.

[0006] In another aspect, embodiments herein relate to a method of making the sulfonic acid modified polyvinyl alcohol resin described above, which may include copolymerizing a vinyl ester monomer with a sulfonic acid comonomer and incorporating a second comonomer to produce the sulfonic acid modified polyvinyl alcohol resin.

[0007] In yet another aspect, embodiments herein relate to inks, paints, paper coatings, emulsions, or films comprising the sulfonated polyvinyl alcohol resins described above.

[0008] Other aspects and advantages of the claimed subject matter will become apparent from the following description and the appended claims. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic diagram depicting the internal structure of an example modified PVOH resin according to one or more embodiments of the present disclosure. [Diagram 2] FIG. 1 is a conceptual diagram illustrating a three-component analysis of the internal structure of a resin by pulsed NMR measurement. [Diagram 3]1 is a graph illustrating sample disintegration times and pulsed NMR component analysis for samples of PVOH resins according to one or more embodiments of the present disclosure. [Figure 4] 1 is a graph illustrating sample disintegration times and pulsed NMR component analysis for samples of PVOH resins according to one or more embodiments of the present disclosure. [Figure 5A] 1 is a table detailing the formulations used to prepare the terpolymers discussed herein. [Figure 5B] 1 is a table detailing the formulations used to prepare comparative homopolymers and copolymers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present disclosure provides compositions and methods for making sulfonic acid modified PVOH resins that have surprisingly been found to have improved solubility in mixtures of water and alcohol.

[0011] Vinyl alcohol copolymers and terpolymers useful in the embodiments disclosed herein can be formed by copolymerizing vinyl ester monomers with one or more selected comonomers via bulk, solution, emulsion, suspension, etc. Vinyl ester monomers (primary monomers) include various fatty acids such as vinyl formate, vinyl acetate, vinyl butyrate, vinyl pivalate, and vinyl versatate, among others.

[0012] The copolymers and terpolymers according to the embodiments herein may contain a first comonomer, i.e., a sulfonic acid-containing comonomer.For the sulfonic acid-modified polymers herein, examples of suitable sulfonic acid comonomers containing sulfonic acid groups include, but are not limited to, vinyl sulfonic acid, allyl sulfonic acid, ethylene sulfonic acid, 2-acrylamido-1-methylpropane sulfonic acid, 2-acrylamido-2-methylpropane sulfonic acid (AMPS), 2-methacrylamido-2-methylpropane sulfonic acid, 2-sulfoethyl acrylate, and salts thereof, among others.In some embodiments, the sulfonic acid-containing comonomer is 2-acrylamido-2-methylpropane sulfonic acid (AMPS).

[0013] The sulfonic acid-containing comonomer may be incorporated into the polymer in an amount ranging from about 0.1 to about 15 mol%, 0.5 to about 10 mol%, or about 1 to about 6 mol%, for example, in other embodiments, from about 2 to about 5 mol% or from about 3 to about 4.25 mol%. In some embodiments, the sulfonic acid-containing comonomer is incorporated in an amount of at least 3.5 mol% or at least 4 mol%. In other words, the sulfonic acid-containing comonomer may be incorporated into the polymer in an amount ranging from a lower limit of 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, or 5 mol% to an upper limit of 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, or 10 mol%, where any lower limit may be combined with any mathematically compatible upper limit.

[0014] When a second or additional comonomer is introduced to produce, for example, a terpolymer of sulfonic acid modified PVOH, suitable comonomers include, but are not limited to, pyrrolidone, carboxylate, or alkyl ester comonomers.

[0015] A PVOH terpolymer comprising a first and a second comonomer may, in some embodiments, comprise from about 0.01 to about 20 mol % of the second comonomer. In other embodiments, the PVOH terpolymer may have from about 0.05 to about 15 mol %, such as from about 0.1 to about 10 mol % or from about 0.1 to about 5 mol % of the second comonomer. In various embodiments, the first comonomer and the second comonomer may each be incorporated into the polymer in an amount ranging from 0.1, 0.2, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, or 5 mol % at the lower limit and from 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 11, 12, 13, 14, or 15 mol % at the upper limit. Here, any lower limit may be combined with any mathematically compatible upper limit.

[0016] The total amount of comonomers incorporated into the polymer, including the sulfonic acid-containing comonomer and the second or additional comonomer, may range from 0.5 to 30 mol%, for example, in various embodiments, from about 1 to about 25 mol%, from about 2 to about 15 mol%, or from about 3 to about 10 mol%. In some embodiments, the total amount of comonomers incorporated into the polymer is an amount having a lower limit of 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, or 5 mol%, and an upper limit of 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 11, 12, 13, 14, 15, 20, 25, or 30 mol%, where any lower limit may be combined with any mathematically compatible upper limit.

[0017] An embodiment of the PVOH terpolymer may include from about 0.1 to about 15 mol% of the second comonomer and from about 0.1 to about 15 mol% of the first comonomer. In some embodiments, the PVOH terpolymer may include from about 0.25 to about 10 mol% of the second comonomer and from about 2 to about 10 mol% of the first comonomer. In other embodiments, the PVOH terpolymer may include from about 0.25 to about 6 mol% of the second comonomer and from about 2 or 3 to about 8 mol% of the first comonomer. In still other embodiments, the PVOH terpolymer may include from about 0.3 to about 5.4 mol% of the second comonomer and from about 3.6 to about 9.4 mol% of the first comonomer. In further embodiments, the PVOH terpolymer comprises from about 0.1, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, or 0.5 mol % to about 1.0, 2.0, 3.0, 3.5, 4.0, 4.5, 5.0, 5.4, 5.8, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10, 12.5, or 15 mol % of a second comonomer and from about 0. and from 1, 0.2, 0.3, 0.4, 0.5, 0.75, 1.0, 1.5, 2.0, 2.5, 3.0, 3.3, 3.6, 4.0, 4.5, or 5.0 mol % to about 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.4, 10.0, 12.5, or 15.0 mol % of the first comonomer, where any lower limit may be combined with any mathematically compatible upper limit.

[0018] Thus, the copolymers according to embodiments herein may contain about 65 to about 99.5 mol% vinyl alcohol (including vinyl ester monomer units, the amount of which depends on the degree of saponification, as known in the art). In other embodiments, the copolymers according to embodiments herein may contain vinyl alcohol (including vinyl ester monomer units, the amount of which depends on the degree of saponification) in an amount ranging from 70, 75, 80, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, or 95 mol% at the lower limit and 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, or 99.5 mol% at the upper limit, where any lower limit may be combined with any mathematically compatible upper limit.

[0019] Suitable pyrrolidone comonomers include those having a polymerizable carbon-carbon double bond and the formula: [ka] (wherein R1, R2, R3, R4, R5, and R6 are each independently selected from a hydrogen atom or an alkyl group, for example, an alkyl group having 1 to 8 carbon atoms.) Examples of the group represented by the general formula (I) include a 2-oxopyrrolidin-1-yl group, a 3-propyl-2-oxopyrrolidin-1-yl group, a 5-methyl-2-oxopyrrolidin-1-yl group, a 5,5-dimethyl-2-oxopyrrolidin-1-yl group, and a 3,5-dimethyl-2-oxopyrrolidin-1-yl group. Examples of the carbon-carbon double bond contained in the pyrrolidone comonomer include a vinyl group, an allyl group, a styryl group, an acryloxy group, a methacryloxy group, a vinyloxy group, and an allyloxy group. These groups are copolymerizable with the vinyl ester of the fatty acid described above, and have high alkali resistance when the copolymer is hydrolyzed to form a vinyl alcohol copolymer. Examples of pyrrolidone comonomers include N-vinyl-2-pyrrolidone (NVP), N-vinyl-3-propyl-2-pyrrolidone, N-vinyl-5-methyl-2-pyrrolidone, N-vinyl-5,5-dimethyl-2-pyrrolidone, N-vinyl-3,5-dimethyl-2-pyrrolidone, and N-allyl-2-pyrrolidone, among others.

[0020] The pyrrolidone comonomer may be incorporated into the polymer in an amount ranging from about 0.25 to about 4 mol%, or from about 0.25 to about 3 mol%, or from about 0.35 to about 2.9 mol% in some embodiments. In some embodiments, the pyrrolidone comonomer is incorporated into the polymer in an amount ranging from 0.25, 0.3, 0.35, 0.5, 0.75, 1, 1.25, 1.5, 1.75, 2, 2.25, or 2.5 mol% at the lower limit and from 2, 2.25, 2.5, 2.75, 2.9, 3, 3.25, 3.5, 3.75, or 4 mol% at the upper limit, where any lower limit may be combined with any mathematically compatible upper limit.

[0021] In some embodiments, the sulfonic acid modified polyvinyl alcohol resin comprises 4-8 mol% of the first comonomer and 0.25-3 mol% of the pyrrolidone comonomer. For example, the sulfonic acid modified polyvinyl alcohol resin in some embodiments comprises 4-6.5 or 7 mol% of the first comonomer and 0.35-2.9 mol% of the pyrrolidone comonomer.

[0022] Suitable carboxylate-containing comonomers include those derived from vinyl carboxylic acid monomers and their esters, including, but not limited to, acrylic acid, crotonic acid, methyl acrylate (MA), methacrylic acid, methyl methacrylate, maleic acid, itaconic acid, dimethyl itaconate, and fumaric acid.

[0023] The carboxylate-containing comonomer may be incorporated into the polymer in an amount ranging from about 0.1 or 0.25 to about 5.4 or 6 mol % in some embodiments, or from about 0.5 to about 3.5 mol % in other embodiments, such as from about 0.75 to about 3.25 mol %, or from about 1 to about 3 mol %. In some embodiments, the carboxylate-containing comonomer is incorporated into the polymer in an amount ranging from 0.25, 0.3, 0.35, 0.5, 0.75, 1, 1.25, 1.5, 1.75, 2, 2.25, or 2.5 mol % at the lower limit and from 2, 2.25, 2.5, 2.75, 3, 3.25, 3.5, 3.75, 4, 4.25, 4.5, 4.75, 5, 5.5, or 6 mol %, where any lower limit may be combined with any mathematically compatible upper limit.

[0024] In some embodiments, the sulfonic acid modified polyvinyl alcohol resin comprises 2 or 3 to 8 mol % of a first comonomer and 0.1 to 6 mol % of a carboxylate-containing comonomer. For example, some embodiments of the sulfonic acid modified polyvinyl alcohol resin comprise 3 to 6.5 or 7 mol % of a first comonomer and 0.25 to 5.4 mol % of a carboxylate-containing comonomer.

[0025] Suitable alkyl ester comonomers include various alkyl esters that contain polymerizable vinyl. Alkyl esters useful according to embodiments herein include: [ka] (In the formula, R1, R2, and R3 are each independently C 1~8 The alkyl group may be an alkyl group such as an alkyl group, and the total number of carbon atoms, R1, R2, and R3, taken together, is from 6 to about 20, so that the monomer unit contains a tertiary substituted carbon. The tertiary alkyl group may have the general structure of a branched ester as shown in Figure 1. Tertiary alkyl groups are very resistant to alkaline hydrolysis, so this structure remains in the polymer after saponification. In some embodiments, the total number of carbon atoms, R1, R2, and R3, taken together, is from 6 to about 12. In other embodiments, the alkyl ester may be a vinyl ester of Versatic acid, such as that sold by Shell Chemical under the trademark VEOVA or by ExxonMobil Chemical as EXXAR neovinyl ester. In some embodiments, a suitable comonomer may include vinyl neodecanoate, such as that sold by Shell Chemical under the trade name VEOVA10.

[0026] The alkyl ester comonomer may be incorporated into the polymer in an amount ranging from about 0.25 to about 4 or 6 mol %, or from about 0.5 to about 3.8 mol %, in some embodiments, such as from about 0.75 to about 3.25 mol %, or from about 1 to about 3 mol %, in other embodiments. In some embodiments, the alkyl ester comonomer is incorporated into the polymer in an amount ranging from 0.25, 0.3, 0.35, 0.5, 0.75, 1, 1.25, 1.5, 1.75, 2, 2.25, or 2.5 mol % at the lower limit and from 2, 2.25, 2.5, 2.75, 3, 3.25, 3.5, 3.75, or 4 mol %, where any lower limit may be combined with any mathematically compatible upper limit.

[0027] In some embodiments, the sulfonic acid modified polyvinyl alcohol resin comprises 2-8 mol% of the first comonomer and 2-6 mol% of the alkyl ester comonomer. For example, the sulfonic acid modified polyvinyl alcohol resin in some embodiments comprises 3-7 mol% of the first comonomer and 0.5-3.8 mol% of the alkyl ester comonomer.

[0028] The vinyl ester monomers and comonomers described above can be copolymerized by bulk polymerization, solution polymerization, emulsion polymerization, suspension polymerization, etc. The vinyl ester copolymer or terpolymer thus obtained may be saponified, and the resulting PVOH copolymer or terpolymer may have a degree of hydrolysis measured according to JIS K6726 in the range of about 65 to about 99% in some embodiments, and in the range of about 75 to about 95% in other embodiments. The resulting PVOH copolymer and terpolymer may be C 13 The hydroxyl content may be at least 65 mole % as measured by NMR analysis. In yet another embodiment, the PVOH copolymer or terpolymer is 13 It may have a hydroxyl unit content of at least about 66 mole percent as indicated by NMR analysis.

[0029] The PVOH copolymers or terpolymers according to the embodiments herein may have a relative molecular weight, as indicated by the characteristic viscosity, in some embodiments, from about 2 to about 60 cps, in other embodiments, from about 10 to about 60 cps, in yet other embodiments, from about 3 to about 50 cps, or in a further embodiment, from about 5 to about 40 cps. In still other embodiments, the PVOH copolymers or terpolymers according to the embodiments herein may have a relative molecular weight, as indicated by the characteristic viscosity, in a range having a lower limit of 2, 3, 5, 7, 10, 12, 12.2, or 15 cps and an upper limit of 40, 50, 55, 57.4, 60, 65, 70, 75, or 80 cps, where any lower limit may be combined with any upper limit. The characteristic viscosity is determined for a 4 wt % aqueous solution of the polymer and is measured at 20° C. using a Brookfield viscometer according to JIS K6726.

[0030] In another aspect, it has been surprisingly found that when sulfonic acid modified PVOH copolymers as described above are prepared to have specific component ratios and relaxation times as measured by pulsed NMR solid echo at 80° C., the copolymers have improved solubility in water-alcohol mixtures. Pulsed NMR characterization is described below and further detailed in the experimental results below.

[0031] 1 is a schematic diagram illustrating the internal structure of an example modified PVOH resin according to one or more embodiments of the present disclosure. As shown in FIG. 1, the internal structure of the resin includes three components: a first component L, a second component M, and a third component S.

[0032] Component S is a component with a short relaxation time in pulsed NMR measurements and is a "hard" component with low molecular mobility. Component L is a component with a long relaxation time in pulsed NMR measurements and is a "soft" component with high molecular mobility. Component M has a relaxation time in pulsed NMR measurements that is between components S and L, and therefore has molecular mobility that is between components S and L.

[0033] In other words, component S corresponds substantially to the crystalline and crosslinked regions of the resin, component L corresponds to the amorphous regions of the resin, and component M corresponds to the "interface" regions of the resin that are between the crystalline and amorphous regions of the resin.

[0034] FIG. 2 is a conceptual diagram for explaining the three-component analysis of the internal structure of a resin by pulsed NMR measurement. By measuring the resin with pulsed NMR, 1 A free induction decay curve of H spin-spin relaxation is obtained. The obtained free induction decay curve can be separated into three components, namely, three curves originating from the hard component S, the medium component M, and the soft component L in ascending order of relaxation time. In other words, the actually measured free induction decay curve can also be obtained by superimposing all three free induction decay curves originating from the above components S, M, and L.

[0035] A method for separating and analyzing the three components using pulsed NMR is known, and examples of the method include DIC Technical Review No. 12 / 2006, “Phase separation structure analysis of polyurethane resin by solid-state NMR (high-resolution NMR and pulsed NMR)” and JP2018-2983A.

[0036] When the sulfonic acid-modified PVOH copolymer as described above was prepared to have specific component ratios and relaxation times measured at 80°C by pulsed NMR solid echo method, the solubility of the copolymer in a water-alcohol mixture was improved.

[0037] In some embodiments, the sulfonic acid modified PVOH copolymer comprises a hard component present in a ratio of 10% to 55% and having a relaxation time of 0.0091 to 0.0104 milliseconds measured by pulsed NMR solid echo at 80° C. In other embodiments, the sulfonic acid modified PVOH copolymer comprises a hard component present in a ratio of 15% to 50% and having a relaxation time of 0.0091 to 0.0102 milliseconds measured by pulsed NMR solid echo at 80° C. In yet other embodiments, the sulfonic acid modified PVOH copolymer comprises a hard component present in a ratio of 16% to 50% and having a relaxation time of 0.0092 to 0.0101 milliseconds measured by pulsed NMR solid echo at 80° C. In various embodiments, the modified polyvinyl alcohol resin comprises a hard component present in a component ratio having a lower limit of 0.1, 0.5, 1, 2.5, 5, 7.5, 10, 11, 12, 13, 14, 15, 16, 17, 18, or 20% and an upper limit of 30, 35, 40, 45, 47.5, 50, 52.5, 55, 57.5, or 60%, where any lower limit may be combined with any upper limit. Additionally, embodiments of the modified polyvinyl alcohol resin may have a hard component with a relaxation time as measured by pulsed NMR solid echo at 80° C., with a lower limit of 0.00905, 0.0091, 0.00915, 0.0092, 0.00925, 0.0093, 0.00935, 0.0094, 0.00945, or 0.0095 milliseconds and an upper limit of 0.0097, 0.00975, 0.0098, 0.00985, 0.0099, 0.01, 0.0101, 0.0102, 0.0103, or 0.0104 milliseconds, where any lower limit may be combined with any upper limit.

[0038] Further, an embodiment of the modified polyvinyl alcohol resin includes a soft component present in a component ratio of 10% to 35% and having a relaxation time of 0.418 to 1.2 milliseconds measured by pulsed NMR solid echo at 80° C. In another embodiment, the modified polyvinyl alcohol resin includes a soft component present in a component ratio of 10% to 33% and having a relaxation time of 0.418 to 1.2 milliseconds measured by pulsed NMR solid echo at 80° C. In yet another embodiment, the modified polyvinyl alcohol resin includes a soft component present in a component ratio of 10.5% to 30% and having a relaxation time of 0.47 to 0.97 milliseconds measured by pulsed NMR solid echo at 80° C. In various embodiments, the modified polyvinyl alcohol resin comprises a soft component present in a component ratio having a lower limit of 9.8, 9.9, 10, 10.5, 10.6, 10.7, 10.8, 11, 11.5, or 12% and an upper limit of 29, 29.5, 30, 31, 32, 33, 34, or 35%, where any lower limit may be combined with any upper limit. Additionally, embodiments of the modified polyvinyl alcohol resin may have a soft component with a relaxation time measured by pulsed NMR solid echo at 80° C. of 0.418, 0.419, 0.42, 0.425, 0.43, 0.44, 0.45, 0.46, 0.47, 0.472, 0.474, 0.476, 0.477, 0.478, 0.479, or 0.48 milliseconds as a lower limit, and 0.79, 0.8, 0.85, 0.9, 0.95, 0.96, 0.97, 0.98, 0.99, 1.0, 1.05, 1.1, 1.15, or 1.2 milliseconds as an upper limit, where any lower limit may be combined with any upper limit.

[0039] The modified polyvinyl alcohol resins of the present disclosure may have improved solubility in mixtures of water and alcohol. The sulfonic acid modified PVOH resins of the present disclosure have been surprisingly found to have improved solubility in mixtures of water and alcohol compared to conventional sulfonic acid modified PVOH resins known in the art. The improved solubility may be demonstrated, for example, by a shorter disintegration time compared to conventional sulfonic acid modified PVOH resins known in the art. The modified polyvinyl alcohol resins of the present disclosure may have a disintegration time of 85 seconds or less, 80 seconds or less, 70 seconds or less, 60 seconds or less, 55 seconds or less, 50 seconds or less, 45 seconds or less, 40 seconds or less, 35 seconds or less, or 30 seconds or less in a mixture of 50 vol.% water and 50 vol.% isopropyl alcohol at 23° C. according to the solution cast disintegration test method. In other embodiments, the modified polyvinyl alcohol resins herein may have a disintegration time of 20 seconds, 22 seconds, 24 seconds, 26 seconds, 28 seconds, or 30 seconds at the lower limit and 50 seconds, 52 seconds, 54 seconds, 56 seconds, 58 seconds, 60 seconds, 70 seconds, 80 seconds, 90 seconds, 100 seconds, or 110 seconds at the upper limit. Here, any lower limit may be combined with any upper limit, and the disintegration time is measured at 23°C according to the solution cast disintegration test in a mixture of 50 vol% water and 50 vol% isopropyl alcohol. For example, the sulfonic acid modified PVOH resins of the present disclosure may have a disintegration time of about 24 to about 54 seconds at 23°C according to the solution cast disintegration test in a mixture of 50 wt% water and 50 wt% isopropyl alcohol.

[0040] As mentioned above, the hard component may be considered as a crystalline or crosslinked portion of the sulfonic acid modified PVOH resin and may represent a polymer portion that may be less soluble in a solvent or a mixed solvent, such as a water / alcohol mixture. The insoluble polymer may be formed by crosslinking during the initial reaction or during processing. However, to maintain high solubility of the resin of the embodiments herein, the resin may be manufactured and processed to have a low or zero gel content. The gel content or gel fraction may be measured, for example, by dissolving a known weight of the resin in a solvent, such as a water-alcohol mixture, and then filtering the sample through a mesh to separate the insoluble and soluble components. After drying the filter residue, the weight of the insoluble resin can be used to calculate the gel fraction (weight of the filter residue divided by the initial weight of the resin). Embodiments of the sulfonic acid modified PVOH resins herein may have a gel fraction, measured in a 50 / 50 (vol%) mixture of water and isopropanol and based on the insoluble portion of a film used in the Solution Cast Disintegration Test described below, of 3.2 or less, 3.0 or less, 2.5 or less, 2.0 or less, 1.5 or less, 1.0 or less, 0.8 or less, 0.6 or less, or 0.5 or less, or may be so low that no gel fraction is present.

[0041] In another aspect, a method for making a sulfonic acid modified PVOH resin with improved solubility in a mixture of water and alcohol may include copolymerizing a vinyl ester monomer with a sulfonic acid comonomer and incorporating one or more second comonomers such that the resulting sulfonic acid modified PVOH resin has one or more of the properties outlined above, such as gel content, disintegration time, first comonomer content, second comonomer content, hard component content and relaxation time, soft component content and relaxation time, degree of hydrolysis, and viscosity.

[0042] As mentioned above, vinyl alcohol copolymers and terpolymers useful in the embodiments disclosed herein can be formed by copolymerizing vinyl ester monomers with one or more selected comonomers via bulk polymerization, solution polymerization, emulsion polymerization, suspension polymerization, etc. The reaction conditions can vary depending on the monomers and comonomers used, and the reaction can be carried out in one or multiple stages.

[0043] Polymerization initiators that generate free radicals may be utilized in the copolymerization reaction, such as 2-ethylhexyl peroxydicarbonate (Trigonox EHP), 2,2'-azobisisobutyronitrile (AIBN), t-butyl peroxyneodecanoate (Trigonox 23), bis(4-t-butylcyclohexyl) peroxydicarbonate, di-n-propyl peroxydicarbonate, di-n-butyl peroxydicarbonate, di-acetyl peroxydicarbonate, di-s-butyl peroxydicarbonate. Essentially any initiator capable of generating free radicals may be used. The amount of polymerization initiator fed to the reaction zone may be, for example, from about 0.0001 to about 1 wt % based on the total amount of reactants added.

[0044] Optionally, acetaldehyde (AcH) can be continuously fed into the reaction zone as a chain transfer agent along with the other components, for example, in an amount of up to about 0.2 wt % based on the total amount of reactants added.

[0045] Typically, the process uses a solvent for the comonomer, polymerization initiator, and copolymer formed in the reaction zone. Suitable solvents include, for example, methanol, ethanol, and propanol. The amount of solvent fed to the reaction zone can be, for example, from about 10 to about 40 wt % based on the total amount of reactants added.

[0046] The amount of the first comonomer and the second comonomer fed to the reaction zone is, for example, about 0.1 to about 30 wt% based on the total amount of reactants added, so as to obtain the composition content of the copolymer or terpolymer described above. In some embodiments, the monomer, the first comonomer, and the second comonomer may be added to the reactor and reacted together, or may be added in stages. For example, a vinyl ester monomer such as vinyl acetate may be added to the reactor, the reaction may be started and continued for a certain period of time, and then the first comonomer and the second comonomer may be added to the reactor.

[0047] The average residence time of the reactants in the reaction zone may be, for example, in the range of about 30 to about 360 minutes, such as in the range of about 30 to about 240 minutes, or in the range of about 60 to about 180 minutes. The reaction temperature may be, for example, about 55°C to about 85°C, such as about 60°C to about 80°C. The pressure in the reaction zone may be atmospheric pressure (about 0 bar gauge (barg) (about 0 psig)) in some embodiments. In other embodiments, the pressure in the reaction zone may be slightly higher than atmospheric pressure, such as in the range of about 0.1 to about 2.1 barg (about 1 to about 30 psig), such as about 0.2 to about 1.1 barg (about 3 to about 15 psig).

[0048] Generally, the residence time and temperature in the reaction zone are such that substantially all of the first and second comonomers fed to the system are polymerized, although a small amount of the vinyl ester added to the system may remain unpolymerized.

[0049] When the resulting copolymers and terpolymers are saponified, the reaction effluent may be fed to a stripping column to remove highly volatile components such as unreacted vinyl ester monomers. The resulting "paste" is then mixed with an aqueous solution of a strong base such as sodium hydroxide (e.g., containing about 10 to about 50 wt% sodium hydroxide) to obtain a base with a caustic mole ratio (CMR) of about 0.01 to about 0.1. If necessary, some volatile alcohol such as methanol is also added to reduce the solids content in the paste to about 30 to about 65 wt%. The resulting mass is then reacted at a temperature of about room temperature (RT, about 22°C) to about 50°C for about 5 minutes to about 24 hours to obtain a hydrolysis rate of acetate groups in the copolymer to hydroxyl groups in the range of about 60 to about 99+%.

[0050] The resulting sulfonated PVOH resins according to embodiments herein may be used in formulations for inks, paints, paper coatings, emulsions, and films. Due to their excellent solubility in water / alcohol mixtures, such sulfonated PVOH resins according to embodiments herein can be used in applications where PVOH-co-AMPS polymers would not normally be usable due to their limited solubility in water / alcohol mixtures.

[0051] (Experimental Methods and Examples) Production of sulfonic acid modified PVOH resins and terpolymers

[0052] The modified PVOH resin samples and comparative samples shown in Tables 1A and 1B below were prepared according to the following methods. In addition to the laboratory prepared samples, comparative commercially available resins were also tested and compared to the embodiments herein. The commercially available resins tested included SELVOL E205 (E205) and SELVOL ULTILOCK 4005 (U4005), each from Sekisui Specialty Chemicals. [Table 1] [Table 2]

[0053] VAM-AMPS-NVP terpolymer (Samples N1 to N17)

[0054] A 5 L reactor was prepared with a stirrer, condenser, thermometer, water bath, and nitrogen inlet. Vinyl acetate monomer (VAM), NVP, 50% aqueous solution of AMPS, and MeOH were charged to the reactor in the amounts listed in Tables 2A and 2B (presented as Figures 5A and 5B). The mixture was well stirred at 150 rpm, and the reactor was heated until the internal temperature reached 65 °C, after which the initiator feed was started using a MeOH solution of tert-butyl peroxyneodecanoate (TRIGONOX23). After 30 min, a 50% aqueous solution of NVP and AMPS was continuously fed. After 150 min, the initiator and comonomer feeds were stopped, then heating and mixing were continued for 1 h, and the reaction was terminated by adding MeOH. The polyvinyl acetate (PVAc) solution was fed to a stripping column, where methanol vapor was introduced to remove unreacted vinyl acetate. The solids content was then adjusted to 35 wt% with methanol. Sodium hydroxide (NaOH, 50% aq) was mixed with methanol to produce a 4 wt% solution, which was then mixed into the polymer solution such that the molar ratio of NaOH to PVAc was 0.02. The mixture was placed in a 40°C water bath for 2 hours, after which the saponified polyvinyl alcohol was ground and then placed in an 80°C oven for 1.5 hours.

[0055] VAM-AMPS-MA terpolymer (sample M1)

[0056] The procedure described above for the VAM-AMPS-NVP terpolymer was followed, except that MA was used instead of NVP as described above, and other conditions were the same as above.

[0057] VAM-AMPS-ITA (samples I1 to I3) and VAM-AMPS-DMI (samples D1 to D3)

[0058] The procedure described above for the VAM-AMPS-NVP terpolymer was followed, except that itaconic acid or the itaconic acid derivative dimethyl itaconate (DMI) was used instead of the NVP described above, and other conditions were the same as above.

[0059] VAM-AMPS-VEOVA10 terpolymer (sample V1, V2)

[0060] The procedure described above for the VAM-AMPS-NVP terpolymer was followed, except that vinyl neodecanoate (VEOVA10) was used instead of the NVP described above, and MeOH was also fed in the delay feed. Other conditions were the same as above.

[0061] VAM-AMPS copolymer (samples A1 and A2)

[0062] The procedure described above for the VAM-AMPS-NVP terpolymer was followed, except that no second comonomer was introduced and only AMPS was used as the comonomer. Additionally, TRIGONOX EHP was used as the initiator.

[0063] VAM-AMPS copolymer (sample A3)

[0064] VAM was fed into the first reactor at 15.7 g / min. AMPS aqueous solution (75%) was fed at 0.81 g / min. Initiator (Trigonox EHP) was fed at 5.73 g / min. In the first reactor, the temperature was maintained at 65°C with an average residence time of 1.5 hours. After reaction in the first reactor, the PVAc solution was discharged and transferred to the second reactor. In the second reactor, the polymer solution was reacted at 65°C for another 1.5 hours. The paste was then discharged and methanol vapor was introduced to remove unreacted vinyl acetate, after which the solid content was adjusted to 35 wt%. Sodium hydroxide (NaOH) and methanol solution (4 wt%) were added to the polymer solution such that the molar ratio of NaOH to PVAc was 0.02. The mixture was placed in a 40°C water bath for 2 hours, after which the saponified polyvinyl alcohol was ground and placed in an 80°C oven for 1.5 hours.

[0065] VAM-NVP copolymer (sample U4005)

[0066] The AMPS aqueous solution described in the above samples A1 and A2 was replaced with NVP. NVP was also fed during the polymerization. TRIGONOX23 was used as the initiator. Other conditions were the same as those of samples A1 and A2.

[0067] A VAM homopolymer (sample E205) was also prepared.

[0068] The above mentioned samples and comparative samples were also polymerized and saponified as detailed in Tables 2A and 2B (presented as Figures 5A and 5B).

[0069] C for Composition 13 NMR method

[0070] 99.9% heavy water C 13 A 5 wt% sample solution was prepared and placed in an NMR tube with a diameter of 5 mm. The measurement conditions were as follows: Temperature: 23℃ Number of scans: 4096 Delay D[1]: 10 seconds

[0071] Solution cast disintegration test method

[0072] The solubility of the samples in Tables 1A and 1B was tested using a solution cast disintegration test method as follows: 51 g of the PVOH resin sample was placed in 249 mL of water and the mixture was stirred. The temperature of the mixture was raised to 93°C to ensure that the PVOH was completely dissolved. After cooling to room temperature, the aqueous solution was cast onto a glass plate and placed in an oven at 80°C for 50 minutes. This casting trial was repeated to obtain a dry film thickness of 50 μm ± 3 μm. The film was conditioned at 23°C and 50% humidity for at least overnight. The film was cut into pieces measuring 4.5 cm x 3.5 cm without defects. A 600 mL beaker (PYREX®, height 124 mm, inner diameter 85 mm) was charged with 250 mL of deionized (DI) water and 250 mL of isopropyl alcohol. The temperature of the solution was adjusted to 22.3-23.0°C. A stirring rod (50 mm long, 9.8 mm diameter) was used to stir the solution so that the bottom of the vortex reached the 400 mL line of the beaker. The sample film was placed in a frame with a 3.5 cm x 2.3 cm opening and the frame was secured in the beaker with a clamp supported by a platform so that the stirred water was forced against the film and it began to bulge and ripple. The disintegration time was recorded as the time from the moment the slide was inserted into the stirred / moving water and IPA mixture to the moment the film first observably broke. This evaluation was performed three times for each sample and the results were averaged. The test results are shown in Tables 3A and 3B below.

[0073] Gel Percentage Test Method

[0074] The films for gel percentage test were prepared in the same manner as the films for solution cast disintegration test. Two pieces of film were cut to 4.5 cm x 3.5 cm without defects and weighed (X1g, X2g). One sample was placed in a 150 °C oven for 1 hour and weighed (Z1g) to calculate the solid content. A 100 mL beaker was prepared and 40 mL of water and 40 mL of IPA were added. The temperature of the solution was adjusted to 22.3-23.0 °C. A stirring rod (25 mm long, 7.5 mm diameter) was used to stir the solution so that the bottom of the vortex reached the 60 mL line of the beaker. The time measurement started when the sample entered the mixed solution. After 10 minutes, the mixture was filtered through a 200 mesh filter and weighed (Yg). The insolubles and mesh were placed in a 150 °C oven for 1 hour. After drying, the filter and gel were measured (Z2g). The gel percentage was calculated as follows, and the results are shown in Tables 3A and 3B below. Solid content A=Z1 / X1 Gel percentage (%) = (Z2-Y) / (A×X)×100 [Table 3] [Table 4]

[0075] In addition to the illustrated legend, in FIG. 3, samples with gel percentages above 3.3% are indicated by open dots. The numbers extending from each dot indicate the measured disintegration time (seconds) for each sample, with the underlined numbers indicating samples with disintegration times equal to or longer than the comparative co-AMPS copolymers. As can be seen from the results in Tables 3A and 3B and FIG. 3, samples N1, N2, N6, N7, N8, N11, N13, and N14 had short disintegration times in a mixture of 50% water and 50% IPA, e.g., only 37 seconds for samples N1, N6, and N11, much shorter than any of the comparative VAM-AMPS copolymer (PVOH-co-AMPS) samples A1-A3. Samples N3, N4, N5, N9, N10, and N12 also showed improved performance. Samples N15 and N16 performed comparable to comparative samples A1-A3. Thus, sulfonic acid modified PVOH with N-vinylpyrrolidone (NVP) comonomer performed better, but not when AMPS monomer was present at less than 4 mol%, as shown by the decreased performance of samples N15, N16, and N17. Surprisingly, it was found that even small amounts of the second comonomer, such as 0.35 mol%, can significantly improve solubility. Equally surprising, it was found that optimal performance occurs when the second comonomer is present in a lower range, such as about 0.1 to about 2 mol%, (more preferably about 0.3 to about 0.8 mol% in the case of NVP). In addition to the illustrated legend, Figure 4 shows samples with gel percentages above 3.3% as open dots. The numbers extending from each dot indicate the disintegration time (in seconds) measured for each sample, with the underlined numbers indicating samples with disintegration times equal to or longer than the comparative co-AMPS copolymer. As can be seen from the results in Tables 3A and 3B and Figure 4, the soft components, which are present in a ratio of 10% to 35% and have a relaxation time of 0.4180 ms to 1.2000 ms, are associated with regions of higher molecular mobility in the polymer, as shown by L in Figure 1, for example, which means that the proportion of such regions is relatively large. It is hypothesized that the main factors affecting the collapse time are the small ratio of hard components and the long relaxation time.Furthermore, when the ratio of the hard component is small and the relaxation time of the hard component is long, the disintegration time should be short if the ratio of the soft component is large and the relaxation time is long. This is because the hard component usually has a stronger effect on the disintegration time than the soft component. Therefore, it can be seen that almost all of the data within the optimal range for the hard component with improved disintegration time is also within the optimal range for the soft component.

[0076] Furthermore, terpolymers of sulfonic acid modified PVOH with methyl acrylate (M1), dimethyl itaconate (D1), itaconic acid (I1), or vinyl neodecanoate (V1) also outperformed the VAM-AMPS copolymer samples A1-A3.

[0077] The alternative secondary structures of the well-performing sample resins that lead to improved disintegration times are described below.

[0078] Pulsed NMR characterization

[0079] As mentioned above, Figure 1 is a schematic diagram illustrating the internal structure of an example modified PVOH resin according to one or more embodiments of the present disclosure. As shown in Figure 1, the internal structure of the resin includes three components: a first component L, a second component M, and a third component S.

[0080] Component S is a component with a short relaxation time in pulsed NMR measurements and is a "hard" component with low molecular mobility. Component L is a component with a long relaxation time in pulsed NMR measurements and is a "soft" component with high molecular mobility. Component M has a relaxation time in pulsed NMR measurements that is between components S and L, and therefore has molecular mobility that is between components S and L.

[0081] In other words, component S corresponds substantially to the crystalline and crosslinked regions of the resin, component L corresponds to the amorphous regions of the resin, and component M corresponds to the "interface" regions of the resin that are between the crystalline and amorphous regions of the resin.

[0082] Similarly, as described above, FIG. 2 is a conceptual diagram for explaining a three-component analysis of the internal structure of a resin by pulsed NMR measurement. By measuring the resin with pulsed NMR, 1 A free induction decay curve of H spin-spin relaxation is obtained. The obtained free induction decay curve can be separated into three components, namely, three curves originating from the hard component S, the medium component M, and the soft component L in ascending order of relaxation time. In other words, the actually measured free induction decay curve can also be obtained by superimposing all three free induction decay curves originating from the above components S, M, and L.

[0083] A method for separating and analyzing the three components using pulsed NMR is known, and examples of the method include DIC Technical Review No. 12 / 2006, “Phase separation structure analysis of polyurethane resin by solid-state NMR (high-resolution NMR and pulsed NMR)” and JP2018-2983A.

[0084] An example of pulsed NMR measurement for a resin is described in detail below.

[0085] After acclimatization for 48 hours at 25°C and 50% humidity, about 600 mg of each powdered PVOH resin sample was placed in a 10 mm diameter glass sample tube (BRUKER, product number 1824511, diameter 10 mm, length 180 mm, flat bottom) and the height was adjusted to 15 mm. This sample was subjected to a second curing treatment at 60°C and 50% humidity for 30 minutes, and then placed in a 20 MHz pulse NMR device (BRUKER "Minispec MQ20") and held at a target temperature of 80°C. The measurement conditions are as follows. Solid echo method Scan: 128 times; Recycle delay: 0.5; Acquisition scale: 1 ms; Temperature: 80℃ This condition is an example. Preferably, the number of scans should be set so that the intensity of the normalized relaxation curve is 0.02 milliseconds or less, and the recycle delay is 5 times the vertical relaxation time T1.

[0086] Obtained 1 The free induction decay curve of H spin-spin relaxation was separated into three curves derived from the above three components S, M, and L. The waveform separation was performed by fitting to both Gaussian and exponential models. The ratio of each component was obtained from the curves derived from the three components obtained in each measurement.

[0087] Using BRUKER's analysis software "TD-NMRA (Version 4.3, Rev. 0.8)," component S was fitted to a Gaussian model, and components M and L were fitted to exponential models according to the product manual for TD-NMRA (Version 4.3, Rev. 0.8). In the analysis, fitting was performed using points up to 0.6 milliseconds on the relaxation curve for the solid echo method.

[0088] The following equation was used for fitting:

number

[0089] Measurement results for selected samples from Tables 1A and 1B above, as also depicted graphically in FIGS. 3 and 4, are presented below with reference to Tables 4A and 4B. [Table 5] [Table 6]

[0090] As can be seen from the data, samples with improved disintegration times in water and IPA mixtures also had a hard component ratio of less than about 55% and a relaxation time of at least 0.0091 milliseconds as measured by pulsed NMR solid echo at 80° C. Alternatively, samples with improved disintegration times had a hard component relaxation time of at least about 0.0092 milliseconds.

[0091] Additionally, samples having a soft component present in a proportion of at least about 10% and having a relaxation time of at least 0.418 milliseconds also exhibited improved disintegration times in a mixture of water and IPA.

[0092] Thus, the present disclosure provides novel modified PVOH resin compositions and methods that result in improved solubility of even sulfonic acid modified PVOH resins in water and alcohol mixtures, thereby introducing the benefits of PVOH-co-AMPS and similar chemistries into new end uses such as inks, paints, paper coatings, emulsions, and film formulations.

[0093] Although only a few exemplary embodiments have been described in detail above, those skilled in the art will readily appreciate that many modifications may be made in the exemplary embodiments without substantially departing from the invention, and all such modifications are therefore intended to be included within the scope of the present disclosure as defined by the following claims.

Claims

1. A sulfonic acid-modified polyvinyl alcohol resin containing 0.1 to 15 mol % of a first comonomer containing a sulfonic acid group, having a hydroxyl unit content of at least 65 mole percent as measured by NMR; The gel fraction is 3.2 or less, a disintegration time of 85 seconds or less as measured at 23° C. in a mixture of 50 vol. % water and 50 vol. % isopropyl alcohol according to the solution cast disintegration test method; The hard component is present in an amount of 10% to 55% and has a relaxation time of 0.0091 milliseconds to 0.0104 milliseconds as measured at 80°C by a pulse NMR solid echo method. Sulfonic acid modified polyvinyl alcohol resin.

2. The sulfonic acid modified polyvinyl alcohol resin according to claim 1, which has a hard component present in a component ratio of 15% or more and 50% or less and has a relaxation time of 0.0091 milliseconds or more and 0.0102 milliseconds or less as measured at 80°C by a pulse NMR solid echo method.

3. 3. The sulfonic acid modified polyvinyl alcohol resin according to claim 1 or 2, comprising a soft component present in a component ratio of 10% or more and 35% or less and having a relaxation time of 0.4180 milliseconds or more and 1.2000 milliseconds or less as measured at 80°C by a pulse NMR solid echo method.

4. 4. The sulfonic acid-modified polyvinyl alcohol resin according to claim 3, wherein the soft component has a relaxation time of 0.47 milliseconds or more and 0.97 milliseconds or less as measured at 80° C. by a pulse NMR solid echo method.

5. The sulfonic acid-modified polyvinyl alcohol resin according to claim 1 or 2, which has a disintegration time of 24 to 54 seconds measured at 23 ° C. according to a solution cast disintegration test method in a mixture of 50 vol % water and 50 vol % isopropyl alcohol.

6. The sulfonic acid modified polyvinyl alcohol resin according to claim 1 or 2, wherein the first comonomer containing a sulfonic acid group contains 2-acrylamide-2-methylpropanesulfonic acid.

7. The sulfonic acid-modified polyvinyl alcohol resin according to claim 1 or 2, which is a terpolymer.

8. 8. The sulfonic acid modified polyvinyl alcohol resin according to claim 7, wherein the terpolymer comprises 0.1 to 15 mol % of a second comonomer selected from the group consisting of pyrrolidone, carboxylate, and alkyl ester, and the alkyl ester is a vinyl ester having tertiary substituted carbons branched with a total of 6 to 20 carbon atoms.

9. The sulfonic acid modified polyvinyl alcohol resin of claim 8, wherein the second comonomer comprises N-vinylpyrrolidone, methyl acrylate, itaconic acid or a derivative of itaconic acid, or vinyl neodecanoate.

10. The sulfonic acid modified polyvinyl alcohol resin according to claim 8, comprising 4 to 8 mol % of said first comonomer and 0.25 to 3 mol % of said pyrrolidone comonomer.

11. 9. The sulfonic acid modified polyvinyl alcohol resin of claim 8, comprising 3 to 8 mole percent of said first comonomer and 0.1 to 6 mole percent of said carboxylate comonomer.

12. The sulfonic acid modified polyvinyl alcohol resin of claim 8, comprising 2 to 8 mol % of said first comonomer and 2 to 6 mol % of said alkyl ester comonomer.

13. 3. The sulfonic acid-modified polyvinyl alcohol resin according to claim 1, which has a gel fraction of 0.6 or less.

14. copolymerizing a vinyl ester monomer with a sulfonic acid comonomer; and Incorporating a second comonomer to produce the sulfonic acid modified polyvinyl alcohol resin of claim 1 or 2. The present invention relates to a method for producing a sulfonic acid-modified polyvinyl alcohol resin having the above structure.

15. 3. An ink, paint, paper coating agent, emulsion, or film comprising the sulfonic acid modified polyvinyl alcohol resin according to claim 1 or 2.